2017
DOI: 10.1021/acs.jpclett.7b01927
|View full text |Cite
|
Sign up to set email alerts
|

Chemical versus Electrochemical Electrolyte Oxidation on NMC111, NMC622, NMC811, LNMO, and Conductive Carbon

Abstract: We compare the stability of alkyl carbonate electrolyte on NMC111, -622, and -811, LNMO, and conductive carbon electrodes. We prove that CO and CO evolution onset potentials depend on the electrode material and increase in the order NMC811 < NMC111 ≈ NMC622 < conductive carbon ≈ LNMO, which we rationalize by two fundamentally different oxidation mechanisms, the chemical and the electrochemical electrolyte oxidation. Additionally, in contrast to the widespread understanding that transition metals in cathode act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
557
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(595 citation statements)
references
References 47 publications
37
557
0
1
Order By: Relevance
“…[219,220] Complementary results were obtained by Bak et al [226] via combined synchrotron-based (time-resolved) XRD and mass spectroscopy. [219,220] Complementary results were obtained by Bak et al [226] via combined synchrotron-based (time-resolved) XRD and mass spectroscopy.…”
Section: In Situ Gas Analyticssupporting
confidence: 59%
See 1 more Smart Citation
“…[219,220] Complementary results were obtained by Bak et al [226] via combined synchrotron-based (time-resolved) XRD and mass spectroscopy. [219,220] Complementary results were obtained by Bak et al [226] via combined synchrotron-based (time-resolved) XRD and mass spectroscopy.…”
Section: In Situ Gas Analyticssupporting
confidence: 59%
“…Apparently, there is a correlation between the oxygen release and the H2-H3 phase transformation, occurring in Ni-rich NCM CAMs at potentials above 4.1 V. Consistent results were also reported for the pure Ni endmember LNO. [101,219,220] During initial high-voltage charging up to 4.5-4.6 V vs Li + /Li of HE-NCM CAMs, Li 2 MnO 3 -like domains are supposed to be activated by extraction of Li and O atoms from the lattice. [227] For Li-rich layered oxides, the O 2 evolution usually occurs at high potentials.…”
Section: In Situ Gas Analyticsmentioning
confidence: 99%
“…However, Jung et al 8,10,44 and Strehle et al 25 proposed another concept for stochiometric and overlithiated layered oxides, respectively, suggesting that CO 2 evolution starting at 4.2 V vs. Li + /Li before the onset of oxygen release is produced by the oxidation of surface impurities, while the released oxygen is suggested to react with the carbonate electrolyte causing CO 2 evolution, consistent with the concomitant rapid increase in CO 2 concentration. While the exact mechanism leading to CO 2 evolution is still subject to ongoing discussions, we will here adopt the mechanistic view proposed by Strehle et MnO 3 , and 2350 μmol/g for 0.50 Li 2 MnO 3 ), bulk oxygen release does not seem to be a feasible mechanism for these overlithiated materials.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 However, it has been shown that all NCM materials show structural instabilities at high state-of-charge (SOC), i.e., at a high degree of delithiation, leading to oxygen release from the near-surface region accompanied by the formation of a resistive surface layer; ultimately, this leads to rapid capacity fading and limits the practical capacity of NCM materials to <200 mAh/g. [8][9][10] * Electrochemical Society Member. * * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
“…Electrolyte (EC/DEC) is electrochemically stable until ~4.8 V with a blank electrode composed of conductive carbon and PVDF. 52, 53 We do not attempt to ascribe a capacity to the CO 2 evolution, as CO 2 is likely evolved from surface Li 2 CO 3 that remains after synthesis. Of note, any non-volatile electrolyte decomposition products that cannot be detected using DEMS could contribute to the irreversible capacity on charge.…”
Section: Resultsmentioning
confidence: 99%